INTEGRATION OF BELIEF IN KAMMA AND RESULT OF KAMMA IN THERAVADA BUDDHIST PHILOSOPHY WITH MAHAKAMMAVIBHANGA SUTTA - อัครศรุติพงศ์, บัวบุษรา (Journal of Paramita, 2019)
The objectives of this thesis were as follows:- 1) to study Kamma and result of Kamma in Buddhist philosophy, 2) to study the principles of Kamma in Mahakammavibhanga Sutta, 3) to integrate the belief of Kamma and the result of Kamma in Buddhist philosophy with Mahakammavibhanga Sutta, 4) to propose a model and create a new knowledge body on ?Integration of the belief in Kamma and the result of Kamma in Buddhist philosophy with Mahakammavibhanga Sutta?. This research is a documentary research and its data are collected from primary sources, such as the Tripitaka, Commentaries, academic documents and other relevant research works. In order to obtain a certain model on integration of the belief in Kamma and the result of Kamma in Buddhist philosophy with Mahakammavibhanga Sutta, in-dept interview is carried on from 9 specialists in Buddhism and philosophy. The result of this research were found as follows:- 1. Kamma has its own duty and session in giving the obvious result to the one who badly behaves or well behaves. That person will definitely reap suffering result and blissful result according to his prier action. 2. Mahakammavibhanga Sutta categorizes Kamma and results of Kamma into 4 kinds referring to 4 kinds of people as follows; firstly, one who commits a sin will be reborn in the planes of loss and woe, evil states, perdition and hell. Secondly, the one who behaves badly will be reborn in blissful states of existence and heaven. Thirdly, the one who behaves well will be reborn in blissful states of existence and heaven, and lastly, the one who behaves well will be reborn in the planes of loss and woe, evil states, perdition and hell. 3.The belief in Kamma and retribution of Kamma in Buddhist philosophy integrated with Mahakammavibhanga Sutta shows that; 1) A person who commits a sin will be reborn in the planes of loss and woe, evil states, perdition and hell because he has done unwholesome continuously from the past to the present. 2) A person who did badly will be reborn in blissful states of existence and heaven because this person did more wholesome in the past existence. The result of wholesome conduct is being so powerful that the bad deeds in this life can not give an effect. 3) A person who behaves well will be reborn in blissful states of existence and heaven because he has done goodness continuously from the past existence to present. Therefore the benefaction will result in being reborn in blissful states of existence and heaven. 4) A person who behaves well will be reborn in the planes of loss and woe, evil states, perdition and hell because this person commits so much sin in the past existence that the sin is still affecting him accordingly. 4.The model and knowledge body on ?Integration of the belief in Kamma and the result of Kamma in Buddhist philosophy with Mahakammavibhanga Sutta indicated that Kamma has its own duty and session in giving the obvious result to the one who did unwholesome or wholesome definitely. The integration with Mahakammavibhanga Sutta is to present states or planes of existence where ones will inevitably reap the fruits of their wholesome and unwholesome actions. The model from the study can be summed up with ?BUM Model?. B refers to belief in Kamma and its result, U is used for understanding of Kamma and the result of Kamma, and M is for meritorious action.